Pendidikan Agama Islam di Perguruan Tinggi: Integrasi Ilmu dan Nilai Spiritual - Jimi Harianto; Dinda Mufida; Reni Aryani; Zahra Saputri (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Islamic Religious Education in higher education frequently experiences a reduction of meaning due to the separation between the mastery of empirical sciences and the cultivation of spirituality, resulting in its position being perceived as a complementary course with limited integration into other academic disciplines. This condition raises both conceptual and practical issues regarding how to design a model of Islamic Religious Education that systematically, applicatively, and contextually integrates scientific knowledge and spirituality within contemporary higher education. This study aims to formulate such an integrative framework through a qualitative approach based on an in-depth literature review of books, journal articles, and research findings, which are analyzed thematically and conceptually. The results identify three main strategies: the development of an interdisciplinary curriculum that internalizes ethical–tawhidic values within professional sciences, the implementation of value-based pedagogy that connects spiritual concepts such as as-sidq and al-amanah with real-life case studies, and the strengthening of campus culture that supports value internalization through co-curricular activities and community service. The synthesis of findings indicates that this integrative model has the potential to enhance students’ moral awareness, spiritual resilience, and ethical decision-making capacity in responding to the dynamics and complexities of modern life. The conclusion emphasizes that the integration of scientific knowledge and spirituality in Islamic Religious Education is not merely a curricular supplement, but a strategic necessity in higher education. The novelty of this study lies in the formulation of a conceptual framework that positions spirituality as an overarching paradigm that provides meaning, direction, and ethical responsibility for the entire structure of knowledge, while offering an applicative model to overcome the dichotomy between secular science and religion in order to produce graduates with strong character, reflective capacity, and a commitment to social responsibility. The theoretical and practical implications of this model are expected to serve as a reference for academic policy development and innovation in Islamic Religious Education learning that is adaptive to global challenges and responsive to the needs of students across contemporary interdisciplinary fields in a sustainable, transformative, and contextually Islamic humanistic value-based manner.